Google+ Ripples: A native visualization of information flow - Fernanda B. Viégas; Martin Wattenberg; Jack Hebert; Geoffrey Borggaard; Alison Cichowlas; Jonathan Feinberg; Jon Orwant; Christopher R. Wren (WWW'13: Proceedings of the International World Wide Web Conference, 2013)
G+ Ripples is a visualization of information flow that shows users how public posts are shared on Google+. Unlike other social network visualizations, Ripples exists as a "native" visualization: it is directly accessible from public posts on Google+. This unique position leads to both new constraints and new possibilities for design. We describe the visualization technique, which is a new mix of node-and-link and circular treemap metaphors. We then describe user reactions as well as some of the patterns of sharing that are made evident by the Ripples visualization.